Sphingosine 1-Phosphate Receptor Modulator Fingolimod (FTY720) Attenuates Myocardial Fibrosis in Post-heterotopic Heart Transplantation - Ahmed, Naseer; Linardi, Daniele; Muhammad, Nazeer; Chiamulera, Cristiano; Fumagalli, Guido; Biagio, Livio San; Gebrie, Mebratu A.; Aslam, Muhammad; Luciani, Giovanni Battista; Faggian, Giuseppe; Rungatscher, Alessio (Frontiers in Pharmacology, 2017)
ABSTRACT Background and Objective: Sphingosine 1-Phosphate (S1P), and S1P receptor modulator fingolimod have been suggested to play important cardioprotective role in animal models of myocardial ischemia/reperfusion injuries. To deeply understand the cardioprotective function of S1P and its mechanism in vivo, we analyse apoptotic, inflammatory biomarkers, and myocardial fibrosis in in vivo heterotrophic rat transplantation model. Methods: Heterotopic heart transplantation is performed in 60 Sprague–Dawley (SD) rats (350-400 grams). The total n=60 heart transplant recipients are categorized into Group A (control) and Group B (Fingolimod treated 1mg/kg i.v.). At baseline with 24 hours after heart transplantation, blood and myocardial tissue are collected for analysis of myocardial biomarkers, apoptosis, inflammatory markers, oxidative stress, and phosphorylation of Akt/Erk signalling pathways. Myocardial fibrosis has been investigated using Masson’s trichrome staining during time span of one day and 30 days, respectively. This is observed after heterotropic heart transplantation. Results: Fingolimod treatment activates are tested as anti-apoptotic, anti-inflammatory pathways following the activation of RISK and SAFE pathways (Reperfusion Injury Salvage Kinase and Survivor Activating Factor Enhancement pathways). This is leaded to decrease cardiomyocyte apoptosis and is used to reduce myocardial oxidative stress. This is resulted to decrease myocardial ischemic in reperfusion injuries. Moreover, the time span of 24 hours and 30 days after transplantation is consider to observe a significant reduction in fibrosis in treated group. This comparison is performed to observe (p<0.001). Moreover, the protective effect is suggested on myocardial fibrosis. Conclusions: Sphingosine1phosphate receptor activation with fingolimod activates anti-apoptotic and anti-inflammatory pathways, leading to improve myocardial salvage. This yield is used to reduce the cardiac fibrosis.